Elevation of Serum Levels of Advanced Glycation End Products in Patients With Non‐B or Non‐C Hepatocellular Carcinoma. Issue 6 (23rd September 2014) - Kan, Hiromi; Yamagishi, Sho‐ichi; Ojima, Ayako; Fukami, Kei; Ueda, Seiji; Takeuchi, Masayoshi; Hyogo, Hideyuki; Aikata, Hiroshi; Chayama, Kazuaki
Abstract : Background: The prevalence of non‐B or non‐C hepatocellular carcinoma (NBNC‐HCC) has been increasing all over the world. Advanced glycation end products (AGE) play a role in the pathogenesis of alcoholic liver injury or nonalcoholic steatohepatitis (NASH). Methods: We examined here whether serum levels of AGE were elevated in NBNC‐HCC patients compared with NASH subjects without HCC and investigated which anthropometric and clinical variables were independent determinants of AGE. Results: Ninety NBNC‐HCC, 56 NASH, and 27 control subjects underwent a complete history and physical examination, determination of blood chemistries, including AGE levels. Serum levels of AGE were significantly higher in NBNC‐HCC patients compared with NASH and control subjects [9.1 ± 2.7, 5.2 ± 1.7, 3.5 ± 1.2 (U/ml), respectively, P < 0.05]. Univariate analysis showed that AGE levels were associated with male ( P < 0.05), age ( P < 0.01), aspartate aminotransferase ( P < 0.05), γ‐glutamyl transpeptidase (GGT) ( P < 0.01), HDL‐cholesterol (inversely, P < 0.01), fasting plasma glucose ( P < 0.01), and HbA1c ( P < 0.05). By the use of multiple stepwise regression analysis, age, GGT, and HDL‐cholesterol (inversely) remained significant and were independently related to AGE levels ( R 2 = 0.406). Conclusion: The present results suggest that AGE might be involved in the pathogenesis of NBNC‐HCC, thereby being a biomarker that could discriminate NBNC‐HCC from NASH.